Methods for extraction, isolation and sequencing of cyclotides and others cyclic peptides with anti-helminthic activities: An overview - Eteme, Olivier Ndogo [UNESP]; Zondegoumba, Ernestine Nkwengoua; Tadayozzi, Yasmin Saegusa [UNESP]; Serafim, Jessica Aparecida [UNESP]; Leite, Wendell Queiroz [UNESP]; de Freitas Genari Severino, Mariane [UNESP]; Vicente, Eduardo Festozo [UNESP] (My University, 2024)
The mortality rate caused by parasitic worms on their hosts is of great concern and studies have been carried out to find molecules to reduce the prevalence, host-parasite interaction, and resistance of parasites to treatments. Existing drugs on the market are very often toxic and have many side effects, hence the need to find new, more active molecules. It has been demonstrated in several works that medicinal plants constitute a wide range of new molecules that can solve this problem. Several works have already been able to demonstrate that cyclic peptides of plant origin have shown good activity in the fight against different types of helminths. Therefore, this review aims to provide a general overview of the methods and techniques of extraction, isolation, activities and mechanisms of action of cyclotides and other cyclic peptides for application in the treatment of helminthic infections.
Keywords: Anti-helminthic; Cyclic peptides; Cyclotides; Medicinal plants